PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN: (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR) - Pocerattu V. Alfonso (P3M Politeknik Negeri Ambon, 2025)
The manufacturing sector, as the backbone of the national economy, faces significant challenges in maintaining sustainable employee productivity, especially considering its contribution to Indonesia's GDP reached 19.9% in 2023 with 13.2 million workers absorbed. The identified gap phenomenon shows that inadequate compensation systems contribute to a 23% decrease in productivity and a 15.2% annual turnover rate in Indonesian manufacturing companies. This research aims to analyze and examine the effect of compensation and work motivation on employee performance in manufacturing companies, both partially and simultaneously, as well as measure the contribution of both variables in explaining employee performance variance. The study employed a quantitative approach with explanatory research design through cross-sectional method on 35 respondents of production department employees in West Java manufacturing companies using purposive sampling technique. The research instrument consisted of structured questionnaires with validated 5-point Likert scale, with data analysis using multiple linear regression through SPSS version 26. The results showed that compensation has a positive and significant effect on employee performance (β=0.189; sig.=0.005<0.05), work motivation has a more dominant effect on performance (β=0.264; sig.=0.001<0.05), and both variables simultaneously have significant effects (F=18.247; sig.=0.000<0.05). The coefficient of determination shows a contribution of 53.3% to employee performance variation. This research concludes that although compensation remains an important factor, work motivation has a more substantial impact on manufacturing employee performance, therefore management needs to prioritize the development of intrinsic motivator factors such as achievement recognition, responsibility enhancement, and sustainable career development programs. Keywords:Compensation, Employee Performance, Human Resources, Manufacturing Industry, Work Motivation